Considerations for the assessment of blast exposure in service members and veterans - Rowland, Jared A.; Martindale, Sarah L. (Frontiers in Neurology, 2024)
Introduction Blast exposure is an increasingly present occupational hazard for military service members, particularly in modern warfare scenarios. The study of blast exposure in humans is limited by the lack of a consensus definition for blast exposure and considerable variability in measurement. Research has clearly demonstrated a robust and reliable effect of blast exposure on brain structure and function in the absence of other injury mechanisms. However, the exact mechanisms underlying these outcomes remain unclear. Despite clear contributions from preclinical studies, this knowledge has been slow to translate to clinical applications. The present manuscript empirically demonstrates the consequences of variability in measurement and definition across studies through a re-analysis of previously published data from the Chronic Effects of Neurotrauma Study 34. Methods Definitions of blast exposure used in prior work were examined including Blast TBI, Primary Blast TBI, Pressure Severity, Distance, and Frequency of Exposure. Outcomes included both symptom report and cognitive testing. Results Results demonstrate significant differences in outcomes based on the definition of blast exposure used. In some cases the same definition was strongly related to one type of outcome, but unrelated to another. Discussion The implications of these results for the study of blast exposure are discussed and potential actions to address the major limitations in the field are recommended. These include the development of a consensus definition of blast exposure, further refinement of the assessment of blast exposure, continued work to identify relevant mechanisms leading to long-term negative outcomes in humans, and improved education efforts.